Effects of George Ohsawa One (Macrobiotic) on Biochemical and Haematological Parameters other than Prothrombin Time and Activated Partial Thromboplastin Time in Rabbits (Medical Forum Monthly, 2024)
Objective: To determine the effects of George Ohsawa One (GO1) on sodium, potassium, calcium, hemoglobin and platelet count in rabbits with and without anticoagulated blood.Study Design: Interventional studyPlace and Duration of Study: This study was conducted at the Department of Pharmacology, Federal Post Graduate Medical Institute and National Health Research Complex, PMRC, Sheikh Zayed Hospital Complex, Lahore from January 2010 to August 2011.Materials and Methods: Forty eight (n=48) male rabbits were included in the study. They were divided into two groups which were further divided into two subgroups each. About 700 grams of GO1 was used in the study.Results: The effect of GO1 on platelet count, hemoglobin, serum sodium, potassium and calcium were found to be insignificant.Conclusion: This work on the effect of GOI is first of its kind on biochemical and hematological parameters other than prothrombin time and activated partial thromboplastin time in rabbits measured quantitatively. Although the use of herbal products may not be dangerous per se, further research work is required to explore the benefits of GO1 on biochemical and hematological parameters before it can safely be used in humans as an anti-hemorrhagic agent.